Spatial Planning Policy Implementation in Controlling Agricultural Land Conversion in Tangerang Regency - Sri Bagus Vita Dewi (International Journal of Social Sciences Review, 2026)
This study is driven by the decline in agricultural productivity resulting from the direct conversion of agricultural land into residential areas, particularly in the northern coastal region (Pantura) of Tangerang Regency, including Sepatan, East Sepatan, Pakuhaji, and Rajeg. The primary objective of this research is to assess the implementation of spatial planning policies in regulating agricultural land conversion, using Merilee S. Grindle’s policy implementation framework, which emphasizes both the content of policy and the context of policy. This study employs a qualitative descriptive approach. The findings indicate that the implementation of Regional Regulation (Perda) No. 13 of 2011 concerning the 2011–2031 Spatial Plan of Tangerang Regency has not been effectively implemented. Several inhibiting factors were identified, including suboptimal dimensions of policy implementation, inadequate communication between government authorities and landowners, as well as monitoring and supervision mechanisms that remain largely procedural and formalistic in nature. Keywords: Policy implementation; Spatial planning; Agricultural land conversion